Understanding emotions - Oatley, Keith (Blackwell, 2006)
"This second edition has been thoroughly updated to reflect the latest research and developments in emotions and includes the following features: cohesive synthesis of evolutionary and cultural approaches to emotion; new chapters on communication of emotion, bodily changes, and appraisal; increased emphasis on interpersonal implications of emotions, including studies of newly discovered expressions and systems of communication; new coverage on moral judgment, individual differences, gene-environment interactions, and positive emotions; new coverage of subjective well-being and pro-social emotions like gratitude and compassion; updated references throughout reflect current research and data, including research on affective neuroscience; and a new design and pedagogical features that include new integrated boxes that depict historical landmarks and historical figures, updated tables, boldfaced terms, and end-of-chapter summaries."--BOOK JACKET.